Redrawing the Diverse of Muslim Politics: Study on Political Attitude of Islamic Political Parties in Indonesia - Muhammad Mufti (Ushuluna: Jurnal Ilmu Ushuluddin, 2023)
Muslim politics is understood as something diverse, dynamic, and far from monolithic. Its diversity cannot be reduced to a simple concept and is influenced by many factors. This article aims to explore the influencing factors that shape the diversity of Muslim political character. Taking the case of Islamic political parties in Indonesia, the largest Muslim country in the world, my argument begins by saying that the most influential factors in the formation of Muslim political character are the local context and experience in which Muslim politics is formed. Muslim politics is implemented in various attitudes, movements, and organizations such as political parties. In the context of Indonesia, there are Islamic political parties with various characteristics as well. But the most dominant today are Islamic political parties that tend to be moderate. Moderate Islamic political parties are considered to have a good vision compared to others.